A daring venture - Camden, Elizabeth 1965- (Bloomington, Minnesota Bethany House, a division of Baker Publishing Group, 2018)
In early 1900s New York, biochemist Doctor Rosalind Werner works to champion a water delivery technology that will fight water-borne illnesses. The fight brings her into contact, and conflict, with newly appointed Commissioner of Water, Nicholas Drake. They wage a public battle over the water controversy-- and a private war against their own attractions. When Rosaline becomes the target of an unknown enemy, the stakes may include her life.
Includes discussion questions.
Keywords: Water-supply -- New York (State) -- New York -- Fiction; Women biochemists -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction; Love stories; Christian fiction; Historical fiction; Romance fiction